2013
DOI: 10.1007/s10484-013-9219-4
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Analysis of the Utility of Adding Cardiorespiratory Biofeedback in the Standard Care of Pregnancy-Induced Hypertension

Abstract: This study examined the efficacy of a cardiorespiratory biofeedback intervention compared to bed rest in the treatment of 47 women diagnosed with pregnancy-induced hypertension (PIH). The investigation consisted of a historical control group with 31 PIH subjects receiving treatment as usual (TAU), bed rest and antihypertensive medications, and an experimental group with 16 PIH subjects receiving TAU and instruction on using a portable respiratory sinus arrhythmia (RSA) biofeedback device once daily until deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…This study also provides additional support for use of HRV-biofeedback as an anxiety-reducing technique during pregnancy, as in our study HRV-biofeedback resulted in a reduction of anxiety, while the pregnant women in the control group reported an increase of anxiety, which is commonly found during pregnancy [51,52,53]. Additionally, we found that the technique can be mastered in a relatively short time, also by pregnant women, which was demonstrated by Cullins et al [27] as well.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This study also provides additional support for use of HRV-biofeedback as an anxiety-reducing technique during pregnancy, as in our study HRV-biofeedback resulted in a reduction of anxiety, while the pregnant women in the control group reported an increase of anxiety, which is commonly found during pregnancy [51,52,53]. Additionally, we found that the technique can be mastered in a relatively short time, also by pregnant women, which was demonstrated by Cullins et al [27] as well.…”
Section: Discussionsupporting
confidence: 81%
“…In a systematic review, Fontein-Kuipers et al [26] demonstrated a small but significant reduction in anxiety and depressive symptoms when pooling three trials using different stress-reducing techniques (i.e., a self-help support book, mindfulness training or acupuncture). HRV-biofeedback has also been tested in two studies for its effect on prenatal stress and birth outcomes [27,28], with positive results. Cullins et al [27] compared a group of women with pregnancy-induced hypertension receiving HRV-biofeedback with a similar historical treatment-as-usual control group and found that gestational age was longer and birth weight at delivery was higher in the HRV-biofeedback group than in the control group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RSA data collection is also far less invasive than other methods for collecting biological data. In fact, with the development of technology to collect ambulatory RSA, it is increasingly feasible to measure RSA data in applied research and clinical settings with minimal or no disruption to the individual (Cullins et al, 2013; Goedhart, de Vries, Kreft, Bakker, & de Geus, 2008; Grossman, Wilhelm, & Spoerle, 2004). …”
mentioning
confidence: 99%
“…While all HRV biofeedback training protocols are designed to stimulate the baroreflex, resonance frequency and 6-bpm slow paced breathing approaches may target different frequencies when adults are taller. Although several researchers train individuals to breathe at their resonance frequency (Lehrer et al, 2004;Lin et al, 2012;Steffen et al, 2017), others simply instruct them to breathe at slower-than-normal rates (Zautra et al, 2010;Cullins et al, 2013). There is compelling evidence that breathing near an individual's resonance frequency -but not at the exact rate -increases RSA amplitude and baroreflex gain compared with other frequencies (Vaschillo et al, 2002(Vaschillo et al, , 2004Lehrer et al, 2020a).…”
Section: The Importance Of Resonance Frequency Assessmentmentioning
confidence: 99%